Evaluation of the utility of different laboratory test-related sarcopenia indices as predictors of lung cancer mortality - Xiaoyan Chen; Shuyue Luo; Lisha Hou; Ming Yang; Qiukui Hao (BMC Geriatrics)
Abstract Objectives We evaluated the utility of routine laboratory test-related sarcopenia indices as predictors of mortality in older patients with primary lung cancer undergoing the first chemotherapy course. Design Retrospective cohort study. Setting West China Hospital, Chengdu, China. Participants This study enrolled primary lung cancer patients ≥ 60 years of age undergoing their first chemotherapy course. Measurements Data on individual patients were obtained from the medical records, while information on survival outcomes was gathered through telephone-based follow-up or local government databases. Using available routine hematological and biochemical test results, this study calculated three sarcopenia-related indices for each patient. These indices included the AST/ALT ratio, neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR). We assessed the relationships between these indices and death using Cox proportional hazards models. Results The study included 926 primary lung cancer patients (71.5% male; median age: 65 years) who underwent their first course of chemotherapy. During the follow-up period (median: 28 months), 563 patients (60.8%) died. In the overall population, there was a significantly higher likelihood of all-cause mortality in patients with an NLR ≥ 2.88 (HR = 1.60, 95% CI = 1.36–1.90, P < 0.001) or a PLR ≥ 125.11 (HR = 1.39, 95% CI = 1.17–1.64, P < 0.001) compared to those with values below these thresholds. However, after adjustment for potential confounding factors, no association was found between NLR or PLR and mortality. After stratification by sex, it was found that both NLR and PLR values were associated with an increased risk of mortality among women (NLR: HR = 2.1, P < 0.001; PLR: HR = 2.42, P < 0.001). Conclusions NLR and PLR, are indicators of sarcopenia and can be easily derived from routine laboratory testing data. These indices can significantly predict mortality in older female patients with primary lung cancer at the start of chemotherapy. Therefore, there is potential practical value in using these indices for assessing patient risk prior to chemotherapy.